Disclosure of Green Banking, Profitability and Company Size on Company Value in Banking in Indonesia - Pratiwi, Asti; Basyith, Abdul; Safitri, Ervita (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study aims to determine the effect of green banking disclosures, profitability and firm size on firm value. The sample used was 11 samples with 55 observations using purposive sampling technique. The data used is secondary data, with the data collection method using content analysis. The analysis technique used is multiple linear regression analysis. The results of the analysis prove (1) disclosure of green banking, profitability and firm size has a positive and significant effect on firm value, (2) disclosure of green banking has a negative and significant effect on firm value, (3) profitability has a positive and significant effect on firm value, and (4) company size has a positive and insignificant effect on firm value